Seabeach Evening Primrose, Oenothera humifusa - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS, 2018)
Seabeach evening primrose is found in beach dunes throughout coastal counties in Florida, west to Louisiana, and as far north as New Jersey. https://edis.ifas.ufl.edu/sg177